Targeting ion channel networks in diabetic kidney disease: from molecular crosstalk to precision therapeutics and clinical innovation - Wang, Wenfeng; Ke, Bi; Wang, Chen; Xiong, Xiaojing; Feng, Xiuyuan; Yan, Hua (Frontiers in Medicine, 2025)
Diabetic kidney disease (DKD), a major microvascular complication of diabetes, is closely associated with functional imbalances in ion channels regulating sodium (Na+), calcium (Ca2+), potassium (K+), and chloride (Cl–). This review systematically examines the roles of ion channels in glomerular filtration barrier dysfunction, tubular reabsorption, and fibrotic processes in DKD, with emphasis on the pathological relevance of sodium-glucose cotransporter 2 (SGLT2), epithelial sodium channels (ENaC), transient receptor potential (TRP) channels, chloride channels, aquaporins (AQPs), and PIEZO channels. We further evaluate the clinical efficacy and challenges of ion channel-targeted therapies, including SGLT2 inhibitors and mineralocorticoid receptor antagonists. Emerging strategies integrating ion channel omics, machine learning, engineered biomaterials, and exosome-based delivery systems are proposed to shift DKD treatment paradigms from disease progression delay to pathological reversal. Interdisciplinary collaboration is critical to achieving personalized precision medicine, offering novel perspectives for DKD diagnosis and management.